Determination of Heavy Metals in Fruit Juices by Flame Atomic Absorption Spectrometry - INCE, HURREM; COSKUN, NIHAT (Asian Journal of Chemistry, 2010)
In this study, direct determination of Cu, Fe, Cr, Mn, Zn, Pb, Na, Mg, Ca and K in commercially available fruit juices in Turkish markets, which are often consumed in daily nutrition, was carried out by using flame atomic absorption spectrometry (FAAS). It was found that the average values were below the tolerance limits of analytes. The detection limits (3σ values, N = 10) lie between 1.8 and 4.7 μg L-1 depending on the element. The results were compared with the average daily intake amounts permitted as well as the values written on the packages.